The role of costing in the introduction and scale‐up of HIV pre‐exposure prophylaxis: evidence from integrating PrEP into routine maternal and child health and family planning clinics in western Kenya. (22nd July 2019) - Roberts, D Allen; Barnabas, Ruanne V; Abuna, Felix; Lagat, Harison; Kinuthia, John; Pintye, Jillian; Bochner, Aaron F; Forsythe, Steven; Gomez, Gabriela B; Baeten, Jared M; John‐Stewart, Grace; Levin, Carol
Abstract: Introduction: Understanding the cost of strategies to reach and deliver pre‐exposure prophylaxis (PrEP) to priority populations is essential to assess the cost‐effectiveness and budget impact of HIV prevention programmes. Providing PrEP through maternal and child health and family planning clinics offers a promising strategy to reach women in high HIV burden settings. We estimated incremental costs and explored the cost drivers of integrating PrEP delivery into routine maternal and child health and family planning services in Kenya. Methods: We conducted a costing study from the provider perspective within the PrEP Implementation for Young Women and Adolescents programme in western Kenya. We identified all within‐ and above‐facility activities supporting PrEP delivery and measured clinical service time using time‐and‐motion studies. We obtained input costs from programme budgets, expenditure records and staff interviews. We estimated changes in costs if creatinine testing were postponed from initiation to first follow‐up visit and if PrEP were prioritized to clients at high HIV risk using a behavioural risk assessment tool. We also projected costs under Ministry of Health (MOH) implementation assuming MOH salaries and programme supervision. We estimated annual numbers of PrEP visits from programme data abstracted from 16 facilities between November 2017 and June 2018. We report the cost per client‐month of PrEP dispensed in 2017 USD. Results: For an annual programme output of 24, 005 screenings, 4198 PrEP initiations and 4427 follow‐up visits, the average cost per client‐month of PrEP dispensed in the study was 26.52. Personnel, drugs and laboratory tests comprised 43%, 25% and 14% of programme costs respectively. Postponing creatinine testing and prioritizing PrEP delivery to clients at high HIV risk reduced total programme costs by 8% and 14% respectively. In the MOH scenario assuming no changes in outputs, the projected cost per client‐month of PrEP dispensed decreased to 16.54 and total programme costs decreased by 38%. Conclusions: Incremental PrEP costs are sensitive to the service delivery strategy used to engage priority populations. Postponing creatinine testing and prioritizing PrEP delivery to clients at high HIV risk may reduce costs. Context‐specific cost data are crucial to assess the cost‐effectiveness and affordability of PrEP delivery models.